2017
DOI: 10.1089/jwh.2016.6224
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk and Protective Behaviors Among Reproductive-Aged Women in the United States

Abstract: Improved HIV behavioral risk-reduction strategies are needed for women. Black women could benefit from interventions that address partnership concurrency. For black women and Latinas, who are more likely to use condoms, further examination of broader social and structural factors as contributors to racial/ethnic gaps are warranted and vital for understanding and decreasing HIV-related disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“… 16 Aholou et al found that black women were more likely to have partners who they perceived to be nonmonogamous and were more likely than women of other racial groups to report protective behaviors such as condom use at last vaginal or anal sex. 15 This is consistent with other studies that have described higher rates of condom use among black women, 17 , 18 suggesting that other social and structural factors contribute to HIV acquisition risk for these women. 16 …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“… 16 Aholou et al found that black women were more likely to have partners who they perceived to be nonmonogamous and were more likely than women of other racial groups to report protective behaviors such as condom use at last vaginal or anal sex. 15 This is consistent with other studies that have described higher rates of condom use among black women, 17 , 18 suggesting that other social and structural factors contribute to HIV acquisition risk for these women. 16 …”
Section: Resultssupporting
confidence: 91%
“… 14 Black women, for example, who may not perceive themselves at risk for HIV have a higher probability of exposure to HIV, despite practicing the same sexual behavior (condom use, number of partners) as other women. 15 Being in a sexual network with higher rates of HIV and STIs coupled with low awareness of partners' status or risk factors, increase the risk of HIV acquisition even with protective sexual behavior. 16 Aholou et al found that black women were more likely to have partners who they perceived to be nonmonogamous and were more likely than women of other racial groups to report protective behaviors such as condom use at last vaginal or anal sex.…”
Section: Resultsmentioning
confidence: 99%
“…Dismantling faulty perceptions about black women's sexuality is key because it perpetuates a view of black women as more “promiscuous,” “irresponsible,” or “reckless” than women of other races/ethnicities, despite research findings that demonstrate otherwise. 6 , 8 , 9 These stereotypes have the potential to bias the research agenda away from addressing SDH to a disproportionate focus on individual behavior. Similarly, these stereotypes create the potential for misperceptions to influence practitioners' assumptions about, interactions with, and recommendations or treatment plans for black women, even outside of the practitioners' awareness or intent.…”
Section: Perceptions Of Black Women's Sexualitymentioning
confidence: 99%
“…The causes of these disparities are complex, extend beyond individual risk behaviors (e.g., condom use), and include social and structural factors, such as inequitable access to health care, stigma, and higher community levels of some sexually transmitted infections (STIs) that increase HIV risk. 6 , 7 Compared with women in other racial/ethnic groups, black women report higher levels of condom use during heterosexual intercourse, 6 , 8 , 9 the primary mode of HIV transmission among women. 4 This underscores that the socioecological environments in which risk behaviors occur may increase black women's risk for HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has demonstrated links between HIV/STI transmission, and social and individual-level factors such as drug and condom use, few have examined unique connections between individual, interpersonal, and environmental experiences on HIV/STI-associated behaviors and sexual health outcomes concurrently. 15,16 Contextualizing these factors and experiences is essential for promoting comprehensive sexual health and wellness strategies that address outcomes across the life span and are inclusive of HIV/-STI prevention and treatment interventions and policies.…”
Section: Introductionmentioning
confidence: 99%